2016
DOI: 10.3389/fnsys.2016.00103
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of Somatosensory Information Shifts from an Early Parallel into a Serial Processing Mode: A Combined fMRI/MEG Study

Abstract: The question regarding whether somatosensory inputs are processed in parallel or in series has not been clearly answered. Several studies that have applied dynamic causal modeling (DCM) to fMRI data have arrived at seemingly divergent conclusions. However, these divergent results could be explained by the hypothesis that the processing route of somatosensory information changes with time. Specifically, we suggest that somatosensory stimuli are processed in parallel only during the early stage, whereas the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
(63 reference statements)
0
16
0
1
Order By: Relevance
“…In the passive condition, the tactile response for both JMD1 and C1 was found in the postcentral gyrus, which corresponds to the primary somatosensory cortex (S1). [8][9][10][11] The occipital areas did not respond to tactile stimuli for both JMD1 and C1. In contrast, the responses in the OBT condition for JMD1 and C1 differed from those in the passive condition.…”
Section: Resultsmentioning
confidence: 99%
“…In the passive condition, the tactile response for both JMD1 and C1 was found in the postcentral gyrus, which corresponds to the primary somatosensory cortex (S1). [8][9][10][11] The occipital areas did not respond to tactile stimuli for both JMD1 and C1. In contrast, the responses in the OBT condition for JMD1 and C1 differed from those in the passive condition.…”
Section: Resultsmentioning
confidence: 99%
“…Somatosensory cortices seem to process information in parallel (Liang et al ., 2011) or serial (Khoshnejad et al ., 2014) manner between brain areas. However, this is still under debate and recent combined fMRI and MEG study demonstrated that early neural activity, first 100 ms after somatosensory stimulus, is best explained by parallel and subsequent activity by serial processing route (Klingner et al ., 2016). It is suggested that insula shares connections with dorsal thalamus (Friedman & Murray, 1986; Augustine, 1996; Dum et al ., 2009) but rather little is known about connections to and from insula.…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli were applied to the index finger of the right and left hand in a pseudorandomized order (403 images, approximately 17 min, stimuli duration 2 s, interstimulus interval ranged between 20 and 30 s, 20 stimuli to the left and 20 to the right hand separately). A similar fMRI paradigm was employed in our previous studies (Brodoehl et al, 2013; Brodoehl et al, 2015a; Klingner et al, 2016).…”
Section: Methodsmentioning
confidence: 99%